Negative V3-declaratives in Finland Swedish - Brandtler, Johan; Håkansson, David (Norsk Lingvistisk Tidsskrift, 2016)
This article is concerned with negative V3-declaratives in the Swedish dialects of Finland. We argue that this peculiar word order is a consequence of syntactic reanalysis: the negative marker has changed from syntactic phrase to syntactic head. Though the negative marker in the standard varieties of Swedish has all the characteristics of a syntactic phrase, the data strongly support a head analysis of the negative marker in some of the Finland Swedish dialects: negation is phonetically reduced, may cliticize to the finite verb, and can combine with other negative elements to yield negative concord. The proposed development of the negative element is in line with the general direction of Jespersen’s (1917) cycle, as proposed also by van Gelderen (2008). Furthermore, our data reveal that negative V3-declaratives are less syntactically restricted and have a wider geographical distribution than has hitherto been assumed in the literature.